Tailoring the photoelectrochemistry of catalytic metal-insulator-semiconductor (MIS) photoanodes by a dissolution method - Loget, G. (Nat Commun, 2019)
Apart from being key structures of modern microelectronics, metal-insulator-semiconductor (MIS) junctions are highly promising electrodes for artificial leaves, i.e. photoelectrochemical cells that can convert sunlight into energy-rich fuels. Here, we demonstrate that homogeneous Si/SiO(x)/Ni MIS junctions, employed as photoanodes, can be functionalized with a redox-active species and simultaneously converted into high-photovoltage inhomogeneous MIS junctions by electrochemical dissolution. We also report on the considerable enhancement of performance towards urea oxidation, induced by this process. Finally, we demonstrate that both phenomena can be employed synergistically to design highly-efficient Si-based photoanodes. These findings open doors for the manufacturing of artificial leaves that can generate H(2) under solar illumination using contaminated water.